Z-oo4 Dentoalveolar effects of slow and rapid maxillary expansions in complete bilateral cleft lip and palate - Mazzon, JGP; Garib, DG; Janson, G; Almeida, AM; Calil, LR; Alves, ACM (ARCHIVES OF HEALTH INVESTIGATION, 2015)
Objectives: The aim of this study was to compare the dentoalveolar effects of slow and rapid maxillary expansions in patients with complete bilateral cleft lip and palate. Methods: Thirty patients with complete bilateral cleft lip and palate diagnosed with maxillary constriction were equally divided into two groups. Group 1 comprised 15 patients treated with Quad-helix, while Group 2 comprised 15 individuals treated with conventional Hyrax expander. Digital dental models were obtained pre-expansion (T1) and 6 months after expansion (T2). Maxillary dental arch transverse dimensions, arch perimeter, arch length and palatal depth were measured. Intergroup and interphase comparisons were performed with t tests and paired t tests, respectively (p<0.05). Results: Slow and rapid maxillary expansions promoted significant and similar increase of arch widths and perimeter. Rapid maxillary expansion caused a significant decreasing on the arch length and palatal depth. Conclusions: Slow and rapid maxillary expansions seem to be similarly effective for the correction of maxillary dental arch constriction in complete bilateral cleft lip and palate patients.